Effect of foliar-applied silicon on photochemistry, antioxidant capacity and growth in maize plants subjected to chilling stress - Ghader HABIBI (Acta Agriculturae Slovenica, 2016)
Low temperature is one of the major adverse climatic factors that suppress plant growth and sustainable agricultural development. In these climate conditions, silicon (Si) can mitigate various abiotic stresses including low temperature. In this study, the roles of foliar-applied silicon (10 mM potassium metasilicate) in enhancing tolerance to chilling stress were investigated in maize (Zea mays ‘Fajr’) plants. The low temperature stress caused significant reduction of plant growth and relative water content; however, Si ameliorated these effects. Si supply in maize exhibited a significantly positive effect on accumulation of free amino acids, and reduced the necrotic leaf area. The decrease in maximum quantum yield of PSII (Fv/Fm) was reversible during recovery, but not in the non-Si-treated leaves. This can be explained by enhancement of protective pigments; carotenoid and anthocyanin leading to the protection of PSII from damage. Additionally, analysis of OJIP transients revealed that Si reduced cold damaging effect on performance index (PIabs) and Fv/Fm through improvement of excitation energy trapping (TR0/CS) and electron transport (ET0/CS) per excited cross-section of leaf. The malondialdehyde (MDA) concentration, which was significantly increased under chilling stress, was decreased by Si. The reduced glutathione and ascorbate concentrations were higher in Si-treated plants as compared to those without application of Si under chilling stress. These results indicated that Si could enhance the chilling stress tolerance of maize plants through improving the biomass accumulation, maintaining a high level of glutathione, ascorbic acid, protein, protective pigments, and enhancing the photochemical reactions. This study also suggests that the foliar-applied Si increases recovery ability from chilling injury.